"I'll Show You My Faith" (James 2:18): Inspiring Models for Exilic Life. (October 2020) - Green, Joel B.
Abraham, Rahab, Job, and Elijah do more than illustrate the various points James wants to make about faithful living. In perhaps surprising ways, they invite imitation, identification, and empathetic association among his audience. James recalls these figures from Israel's past so as to encourage his readers and auditors to respond to the rigors of exilic life with comparable patterns of faith and practice.